2020
DOI: 10.3390/ijms21030858
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Germline Genetics on Tacrolimus Pharmacokinetics and Pharmacodynamics in Allogeneic Hematopoietic Stem Cell Transplant Patients

Abstract: Tacrolimus exhibits high inter-patient pharmacokinetics (PK) variability, as well as a narrow therapeutic index, and therefore requires therapeutic drug monitoring. Germline mutations in cytochrome P450 isoforms 4 and 5 genes (CYP3A4/5) and the ATP-binding cassette B1 gene (ABCB1) may contribute to interindividual tacrolimus PK variability, which may impact clinical outcomes among allogeneic hematopoietic stem cell transplantation (HSCT) patients. In this study, 252 adult patients who received tacrolimus for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 74 publications
3
29
1
Order By: Relevance
“…Despite the fact that monitoring blood trough concentrations is an effective method for adjusting tacrolimus oral doses, clinical studies have reported that it may not be valuable for future dosage estimation and may also not be an accurate assessment of overall drug exposure among various individuals [ 17 , 23 , 24 , 25 , 26 ]. It is sometimes challenging to achieve and maintain target tacrolimus trough concentrations despite periodic tacrolimus TDM [ 3 ]. Hence, the determination of the area under the curve (AUC) over a dosing interval is generally considered the best indicator of optimal dosing, though multiple blood samples may be required, which, for practical and financial reasons, limits its clinical utility [ 38 ].…”
Section: Intra-individual and Inter-individual Tacrolimus Pk Variamentioning
confidence: 99%
See 4 more Smart Citations
“…Despite the fact that monitoring blood trough concentrations is an effective method for adjusting tacrolimus oral doses, clinical studies have reported that it may not be valuable for future dosage estimation and may also not be an accurate assessment of overall drug exposure among various individuals [ 17 , 23 , 24 , 25 , 26 ]. It is sometimes challenging to achieve and maintain target tacrolimus trough concentrations despite periodic tacrolimus TDM [ 3 ]. Hence, the determination of the area under the curve (AUC) over a dosing interval is generally considered the best indicator of optimal dosing, though multiple blood samples may be required, which, for practical and financial reasons, limits its clinical utility [ 38 ].…”
Section: Intra-individual and Inter-individual Tacrolimus Pk Variamentioning
confidence: 99%
“…In the modern era, there has been increasing interest in the identification and validation of genetic variations that contribute to IPV [ 72 , 73 ]. Germline mutations in ATP-binding cassette B1 gene (ABCB1) and CYP3A4/5 probably contribute to interindividual tacrolimus PK variability [ 3 , 17 , 74 ]. Single nucleotide polymorphisms (SNPs) in CYP3A5 could contribute 40%–50% of inter-individual PK variability [ 75 , 76 ].…”
Section: Intra-individual and Inter-individual Tacrolimus Pk Variamentioning
confidence: 99%
See 3 more Smart Citations